2018
DOI: 10.3892/mmr.2018.8574
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin inhibits glycolysis in esophageal squamous cell carcinoma by regulating hexokinase‑2 expression

Abstract: Capsaicin is a principal component of hot red peppers and chili peppers. Previous studies have reported that capsaicin exhibits antitumor functions in a variety of tumor models. Although various mechanisms underlying the capsaicin‑mediated inhibition of tumor growth have been demonstrated, the impact of capsaicin on tumor metabolism has rarely been reported. The present study demonstrated that capsaicin exhibited an inhibitory effect on tumor glycolysis in esophageal squamous cell carcinoma (ESCC) cells. Follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“… Liu et al (2019) found that the stem cell characteristics and abnormal metabolic reprogramming of esophageal cancer stem cells were dependent on the Hsp27-AKT-HK2 pathway, and ESCA patients with overexpression of Hsp27 and HK2 in tumor tissues had the worst prognosis. Mao et al (2018) found that inhibiting the expression of HK2 could significantly inhibit the glycolytic effect of ESCA and affect the proliferation of cancer cell. Nevertheless, there are few reports on other biological functions of HK2 in ESCA.…”
Section: Discussionmentioning
confidence: 99%
“… Liu et al (2019) found that the stem cell characteristics and abnormal metabolic reprogramming of esophageal cancer stem cells were dependent on the Hsp27-AKT-HK2 pathway, and ESCA patients with overexpression of Hsp27 and HK2 in tumor tissues had the worst prognosis. Mao et al (2018) found that inhibiting the expression of HK2 could significantly inhibit the glycolytic effect of ESCA and affect the proliferation of cancer cell. Nevertheless, there are few reports on other biological functions of HK2 in ESCA.…”
Section: Discussionmentioning
confidence: 99%
“…Although the concentration of sulforaphane used in our study cannot be reached in vivo through consumption of broccoli in a normal diet, it could be attained through the intake of a diet rich in myrosinase-treated broccoli or sulforaphane-based nutraceuticals. Myrosinase is a temperature sensitive enzyme that converts glucoraphanin from broccoli into sulforaphane [55]. In fact it has been shown that increased sulforaphane bioavailability can be attained after the intake of sulforaphane-enriched broccoli sprout preparation (generated by quick steaming followed by myrosinase treatment) in mice [56].…”
Section: Discussionmentioning
confidence: 99%
“…Many different types of tumors, including breast cancer, kidney cancer, lung cancer, prostate cancer and colorectal cancer, have differences in metabolism [30][31][32][33]. The process of glucose metabolism in tumor cells is signi cantly different from that in normal cells [34,35]. Studies have pointed out that in tumor cells, the mitochondria that produce energy are damaged, hence, most tumor cells use glucose and amino acids as substrates.…”
Section: Discussionmentioning
confidence: 99%